Characterizing creative scientists in nano S & T: productivity, multidisciplinarity, and network brokerage in a longitudinal perspective - Thomas Heinze; Gerrit Bauer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2006)
While some believe that publication and citation scores are key predictors of breakthroughs in science, others claim that people who work at the intersection of scientific communities are more likely to be familiar with selecting and synthesizing alternatives into novel ideas. This paper contributes to this controversy by presenting a longitudinal comparison of highly creative scientists with equally productive researchers. The sample of creative scientists is identified by combining information on science awards and nominations by international peers covering research accomplishments in the mid-1990s. Results suggest that it is not only the sheer quantity of publications that causes scientists to produce creative pieces of work. Rather, their ability to effectively communicate with otherwise disconnected peers and to address a broader work spectrum also enhances their chances to be widely cited and to develop novel ideas.
urn:nbn:de:0011-n-494723
Keywords: 330; Kreativität; Wissenschaftler; Publikationsanalyse; Kritik